Posthumous Reception of Ursula K. Le Guin in Serbian Scholarly Journals and Literary Periodicals - Panajotović, Artea D.; Vučković, Mirjana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Since the 1980s, Ursula K. Le Guin (1929–2018), one of the most influential science fiction and fantasy writers, has had an almost cult status and loyal readership in the region of former Yugoslavia. However, some ten years before her departure, interest in her work decreased. Her most important titles were out of print, new editions were not available, and she was less frequently written about in Serbian journals and periodicals. This changed after her death when, as was to be expected, interest in her work was rekindled. In this paper, we present the critical reception of Ursula K. Le Guin’s work in Serbian scholarly journals and literary periodicals from her death in January 2018 until the end of 2020. The aim of the research is to establish the extent and the way in which her opus (and, with it, speculative fiction in general) was presented and evaluated in Serbian scholarly journals and literary periodicals of this period. The presented results are part of a future, larger diachronic research of the complete reception of Ursula K. Le Guin’s opus in former Serbo-Croatian-speaking territory. Based on the analysed material, Ursula K. Le Guin received significant posthumous reception in Serbian scholarly journals and literary periodicals – in total, 21 texts were published from January 22, 2018, until December 31, 2020. The quality of the academic articles does not differ from the quality of Serbian scholarly production in general, and they examined the work of Ursula K. Le Guin from feminist, postcolonial, and cultural points of view.